Atomic-Scale Design of High-Performance Pt-Based Electrocatalysts for Oxygen Reduction Reaction - Ying, Jie (Frontiers in Chemistry, 2021)
Fuel cells are regarded as one of the most promising energy-conversion devices because of their high energy density and zero emission. Development of high-performance Pt-based electrocatalysts for the oxygen reduction reaction (ORR) is vital to the commercial application of these fuel cell devices. Herein, we review the most significant breakthroughs in the development of high-performance Pt-based ORR electrocatalysts in the past decade. Novel and preferred nanostructures, including biaxially strained core-shell nanoplates, ultrafine jagged nanowires, nanocages with subnanometer-thick walls and nanoframes with three-dimensional surfaces, for excellent performance in ORR are emphasized. Important effects of strain, particle proximity and surface morphology are fully discussed. The remaining changes and prospective research directions are also proposed.